1990
DOI: 10.1002/art.1780330102
|View full text |Cite
|
Sign up to set email alerts
|

The effect of folic acid supplementation on the toxicity of low‐dose methotrexate in patients with rheumatoid arthritis

Abstract: Thirty-two patients with rheumatoid arthritis completed a 24-week, placebo-controlled, double-blind trial of folic acid (FA) supplementation during low-dose methotrexate (MTX) therapy. Administration of the daily FA supplement significantly lowered toxicity scores without affecting efficacy, as measured by joint counts, joint indices, and patient and physician evaluation of disease activity. Fifteen patients experienced some sort of toxicity; 67% were in the placebo group, and 33% were in the FA supplement gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
95
0
10

Year Published

1996
1996
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 237 publications
(110 citation statements)
references
References 44 publications
4
95
0
10
Order By: Relevance
“…However, the effect of methotrexate treatment on lymphocyte proliferation and apoptosis in patients is transient (Յ48 hours) and is reversed by folic acid. In contrast, the antiinflammatory effects of methotrexate are lasting and are not reversed by either folic acid or folinic acid (17)(18)(19)(20)(21)(22). Previous research in animal models has demonstrated that low-dose methotrexate treatment promotes intracellular accumulation of AICAR, an intermediate in purine synthesis, and that accumulation of AICAR is associated with increased adenosine release into inflammatory exudates (1,23); adenosine mediates the antiinflammatory effects of methotrexate treatment in animal models of both acute inflammation and adjuvant arthritis (1,2,24).…”
Section: Discussionmentioning
confidence: 99%
“…However, the effect of methotrexate treatment on lymphocyte proliferation and apoptosis in patients is transient (Յ48 hours) and is reversed by folic acid. In contrast, the antiinflammatory effects of methotrexate are lasting and are not reversed by either folic acid or folinic acid (17)(18)(19)(20)(21)(22). Previous research in animal models has demonstrated that low-dose methotrexate treatment promotes intracellular accumulation of AICAR, an intermediate in purine synthesis, and that accumulation of AICAR is associated with increased adenosine release into inflammatory exudates (1,23); adenosine mediates the antiinflammatory effects of methotrexate treatment in animal models of both acute inflammation and adjuvant arthritis (1,2,24).…”
Section: Discussionmentioning
confidence: 99%
“…More specifically, these studies have investigated the relationship between folic acid and the toxicity of these agents and have concluded that the addition of folic acid significantly reduces toxicity while preserving the antitumor activity of the drug. In a study conducted by Morgan et al [41], patients with rheumatoid arthritis who were given a combination of MTX and folic acid experienced less than half the toxicities as compared to those toxicities seen in the placebo group.…”
Section: Safety and The Addition Of Folic Acid And Vitamin B 12mentioning
confidence: 98%
“…Although pemetrexed has clinically significant activity in a number of tumor types, the high incidence of hematological toxicity as well as treatment-associated fatalities associated with this antifolate has, until recently, limited its prospects as a major antitumor agent. Studies with other antifolates inhibiting DHFR and TS have suggested that poor nutritional status contributes to the likelihood that a patient will experience severe toxicity when exposed to these drugs [41][42][43][44]. More specifically, these studies have investigated the relationship between folic acid and the toxicity of these agents and have concluded that the addition of folic acid significantly reduces toxicity while preserving the antitumor activity of the drug.…”
Section: Safety and The Addition Of Folic Acid And Vitamin B 12mentioning
confidence: 99%
“…RA patients taking MTX are more likely to discontinue treatment because of adverse reactions than because of lack of efficacy (71). Stomatitis, nausea, diarrhea, and perhaps, alopecia caused by MTX may decrease with concomitant folic acid (81,82) or folinic acid (83) treatment without significant loss of efficacy. Relative contraindications for MTX therapy are preexisting liver disease, renal impairment, significant lung disease, or alcohol abuse.…”
Section: Pharmacologic Treatment Of Ramentioning
confidence: 99%